Hukuman Mati Bagi Tindak Pidana Narkoba di Indonesia: Perspektif Sosiologi Hukum - Purnomo, Agus (Fakultas Syariah, 2016)
This paper presents a variety of public opinion on the application of the death penalty for perpetrators of acts of drugs in Indonesia. The study was focused on public dissent in response to the execution of the death penalty for drug crime and efforts to formulate effective criminal penalties for drug crimes. This paper study it from the angle of sociology of law in particular the theory of behaviorism and the theory of justice. In the perspective of sociology of law, a punishment device should include two things: first, it must accommodatepublic aspirations as the counterbalancing repay on the basis of an error rate of the perpetrator. Second, it must include the purpose of punishment, ie, maintain and preserve theunity of the community. Thus, the law must represent the public sense of justice. Hence theattitude and actions of the Indonesian people who chose the death penalty for criminal drugcan be justified even in other countries have abolished the death penalty.Tulisan ini menyajikan beragam pendapat masyarakat tentang penerapan hukuman matibagi pelaku tindak narkoba di Indonesia. Kajian difokuskan pada perbedaan pendapatmasyarakat dalam menyikapi eksekusi pidana mati bagi pelaku pidana narkoba dan upayamerumuskan hukuman pidana yang efektif bagi kejahatan narkoba. Tulisan ini mengkajinyadari sudut sosiologi hukum khususnya teori behaviorisme dan teori keadilan. Dalamperspektif sosiologi hukum, sebuah perangkat pemidanaan hendaknya mencakup dua hal,yakni: pertama, harus menampung aspirasi masyarakat yang menuntut pembalasan sebagaipengimbangan atas dasar tingkat kesalahan si pelaku. Kedua, harus mencakup tujuanpemidanaan, yakni memelihara dan mempertahankan kesatuan masyarakat. Dengandemikian, hukum harus mewakili rasa keadilan masyarakat. Karenanya sikap dan tindakanmasyarakat yang memilih hukuman mati bagi pelaku tindak pidana narkoba dapat dibenarkan sekalipun di tempat lain hukuman mati ini dihapuskan.